Traditional Knowledge and Efficacy Analysis of an Emerging Medicinal Food Plant: Disporopsis aspersa - Qingyu Chen; Miaomiao Wang; Xian Hu; Jihai Zhang; Qing Zhang; Congli Xu; Chunlin Long (Foods)
Disporopsis aspersa (Hua) Engl. ex K. Krause, locally known as kucai (bitter greens) or yexiahua, is a widely consumed wild vegetable and traditional herbal medicine in western Yunnan. Despite its local significance, its nutrient composition and bioactive properties have not been investigated. This study aims to determine the nutritional content and evaluate the antioxidant and anti-inflammatory activities of the aerial parts extracts of D. aspersa. The levels of protein, amino acids, vitamins, and minerals were measured and compared to those of common vegetables. The results showed that D. aspersa contains 16 amino acids, with a total content of up to 19.13 g/100 g, including 3.0 g/100 g of lysine. In vitro evaluations of its antioxidant and anti-inflammatory activities demonstrated that the ethanolic extract exhibited low cytotoxicity against mouse RAW 264.7 murine macrophages cell line at concentrations of 0–120 μg/mL. The IC50 for nitric oxide (NO) scavenging activity was 72.7 ± 7.43 μg/mL, showing dose dependence. Additionally, the ethanolic extract also exhibited ABTS+· scavenging capacity and total antioxidant capacity. These findings suggest that D. aspersa is rich in carbohydrates, fat, dietary fiber, and amino acids. It also contains various bioactive substances, supporting its traditional practices for both medicinal and dietary purposes by local people. D. aspersa has the potential to be developed into a novel anti-hypertensive food, nutraceutical, or dietary supplement in western Yunnan and neighboring regions, promoting local development.